Developing ArVo: Augmented Reality-Based Application to Improve Arabic Vocabulary Mastery - Cahyani, Aisyah; Kholisin, Kholisin (Arabiyatuna: Jurnal Bahasa Arab, 2022)
The purpose of this study was to describe: (1) the process and results of ArVo development and (2) the effectiveness of ArVo to improve students' vocabulary mastery at MAN Kota Batu. Learning media could be used to stimulate students’ reasoning, interests, emotion, and expertise or skills and could accelerate the development of learning processes. The subjects of this study were the students of class X MAN Kota Batu, and they were also accompanied by material experts, media experts, and subject teachers who played certain roles in achieving research’s objectives and quality. This study used 4 data collection techniques, namely observation, interviews, qualitative questionnaires, and quantitative questionnaires with tests. The results showed that the ArVo process and development were carried out based on the 4 data collection techniques, resting upon the ADDIE development model. The effectiveness of ArVo was known based on the assessment results answered by 30 respondents. Such effectiveness indicated an increase in vocabulary mastery and accurate pronunciation.